2021
DOI: 10.1108/wjemsd-07-2020-0073
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing innovative work behaviour in higher institutions of learning: the role of hope

Abstract: PurposeDespite the current dynamism in the education sector that was manifested in new approaches to work that require innovative workforce, little empirical studies have been conducted on how to influence innovativeness in higher education institutions. Moreover, though studies have established a link between hope and innovative work behaviour, no study has established how hope and its two components of agency and pathways influence innovative work behaviour. The purpose of this study is to establish the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…Some scholars (Bunce & West, 1995;Janssen, 2000;Scott & Bruce, 1994;Messmann & Mulder, 2020) advocate the unidimensionality of IWB, which is criticized by others advancing its multidimensionality. Some (Zainal & Mohd Matore, 2021); organizational learning and organizational commitment (Wahyuni et al, 2021); well-being (Ibrahim et al, 2021); hope (Namono et al, 2021); human resource practices (Zreen et al, 2021); digital learning orientation and readiness for change (Aboobaker & Zakkariya, 2021); reflection (Messmann & Mulder, 2015); and leadership style (Khan et al, 2020). Although these studies hint at the importance of job autonomy and exposure to inno- anywhere and anyhow (Moll, 2015).…”
Section: Innovative Work Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars (Bunce & West, 1995;Janssen, 2000;Scott & Bruce, 1994;Messmann & Mulder, 2020) advocate the unidimensionality of IWB, which is criticized by others advancing its multidimensionality. Some (Zainal & Mohd Matore, 2021); organizational learning and organizational commitment (Wahyuni et al, 2021); well-being (Ibrahim et al, 2021); hope (Namono et al, 2021); human resource practices (Zreen et al, 2021); digital learning orientation and readiness for change (Aboobaker & Zakkariya, 2021); reflection (Messmann & Mulder, 2015); and leadership style (Khan et al, 2020). Although these studies hint at the importance of job autonomy and exposure to inno- anywhere and anyhow (Moll, 2015).…”
Section: Innovative Work Behaviourmentioning
confidence: 99%
“…Despite the importance of IWB in higher education institutions, studies have only recently tried to identify the predictors and determinants thereof, such as job autonomy, reward and recognition and work engagement (Dixit & Upadhyay, 2021); job autonomy and job commitment (Baharuddin et al, 2019); management support and exposure to innovation (Lambriex‐Schmitz et al, 2020b); teachers' self‐efficacy and school administrators' transformational leadership practices (Zainal & Mohd Matore, 2021); organizational learning and organizational commitment (Wahyuni et al, 2021); well‐being (Ibrahim et al, 2021); hope (Namono et al, 2021); human resource practices (Zreen et al, 2021); digital learning orientation and readiness for change (Aboobaker & Zakkariya, 2021); reflection (Messmann & Mulder, 2015); and leadership style (Khan et al, 2020). Although these studies hint at the importance of job autonomy and exposure to innovation among other factors as key predictors of IWB, none explore how compulsory NWW practices during COVID‐19 are related to faculty members' IWB in higher education institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wahunyi et al ( 2021) studied innovative behaviors of lecturers in relation with organizational learning and organizational commitment and found that they both have a positive direct influence on the innovative behavior of lecturers. Namono et al (2021) also found that academics and staff members who possess the psychological characteristics of hope exhibit innovative behavior. Faculty members' perceptions of performance appraisal quality relationship have also been found to be effective in promoting their innovative behavior (Waheed, Abbas, & Malik, 2018).…”
Section: Employee's Innovative Behaviormentioning
confidence: 91%
“…Further, beyond the context of individuals' life in general, the extant literature provides ample evidence to suggest that individuals' hope is positively associated with desirable outcomes that are of interest to organizations' performance such as financial performance (Peterson and Luthans, 2003) and profitability at firm/unit level (Luthans et al, 2007;Reichard et al, 2013). Besides such findings at the firm level, previous research across countries, industries and work settings also suggests that hope is positively associated with many other valued outcomes from employees at work, such as innovative work behaviour (Namono et al, 2021), creativity (Rego et al, 2012), knowledge sharing and knowledge creation (Goswami and Agrawal, 2020), work engagement (Ozyilmaz, 2020), job involvement (Ullah et al, 2022) and employee retention (Peterson and Luthans, 2003); hope is negatively associated with absenteeism (Avey et al, 2006), burnout and stress (Reichard et al, 2013).…”
Section: Hopementioning
confidence: 99%
“…Of these, many explored its impact on employee behaviours and organizational outcomes as reviewed in the next section. Although the literature suggests that organization interventions could enhance hope, empirical studies involving specific organization interventions to enhance hope are rare (for review Namono et al, 2021;Wandeler et al, 2017;Zhong et al, 2021). According to Luthans et al (2007), hope is a unique psychological capital valuable to be possessed by any individual, a valuable resource in work settings, and it is identified as malleable to development.…”
Section: Introductionmentioning
confidence: 99%